The Effect of Live Student’ Worksheet to Increase Students' Scientific Literacy in Science Subjects: A Review - Paspania, Karima; Susilawati, Susilawati (International Journal of Science Education and Science, 2024)
This literature study aims to examine the effect of live students’ worksheet interactive on students' ability to increase scientific literacy in science lessons. Search for literature study articles obtained to meet the inclusion criteria and be relevant for review. This research uses secondary data obtained from not direct observation. The data collection method used is the documentation method by searching for data from literature related to the research. Students’ worksheet interactive assisted by live worksheets can increase students' scientific literacy, in addition it can also increase students' creativity, critical thinking and scientific studies of science lessons.